A study on the correlation between remnant cholesterol and urinary albumin to creatinine ratio in Chinese community adults: A report from the REACTION study - Li, Binqi; Wang, Anping; Wang, Yuxia; Li, Lin; Li, Bing; Yang, Zizhong; Zhou, Xin; Gao, Zhengnan; Tang, Xulei; Yan, Li; Wan, Qin; Wang, Weiqing; et al. (Journal of diabetes, 2020)
Background The correlation between remnant cholesterol (RC) and urinary albumin to creatinine ratio (UACR) has not been illustrated. The present study aims to explore the correlation between RC levels and UACR in Chinese community adults. Methods This study included 35 848 participants from a cohort study (REACTION). The UACR data were divided into three groups: UACR <10 mg/g, 10 ≤UACR<30 mg/g, and UACR ≥30 mg/g groups. RC was divided into two groups, according to the 75th percentile: <75% group and ≥75% group. Multiple logistic regression analysis was used to evaluate the correlation between RC and UACR. Results The RC exhibited an adjusted odds ratio that was significant in models 1‐5. Although all confounders were corrected in model 5, RC and UACR were still significantly correlated， and the correlation was more significant in females，when compared to males (odds ratio [OR]: 1.117, 95% CI: 1.063‐1.176, P < 0.001 for all subjects; OR: 1.092, 95% CI: 1.128‐1.161, P = 0.004 for females; and OR: 1.085, 95% CI: 0.998‐1.194, P = 0.088 for males). The RC was significantly correlated with UACR for subjects with 5.6 ≤ fasting blood glucose < 7.0 or 7.8 ≤ post‐load blood glucose < 11.1 mmol/L, 24 ≤ body mass index (BMI) < 28 kg/m2, 120 ≤ systolic blood pressure < 140 and/or 80 ≤ diastolic blood pressure < 90 mm Hg. Conclusions In the Chinese community, RC is highly correlated with UACR, and the correlation is more significant in females compared with males. At higher RC levels, patients with critical values of blood pressure, BMI and blood glucose have a more significant correlation between RC and UACR. 摘要 背景 残余胆固醇(RC)和尿白蛋白肌酐比值(UACR)之间的相关性尚未被阐明。本研究旨在探讨中国社区成年人群中RC水平与UACR的相关性。 方法 本研究纳入来自一个队列研究(REACTION研究)的35848名参与者。UACR分为三组: UACR< 10 mg/g、 10≤UACR<30 mg/g和UACR≥30 mg/g组。根据第75百分位，RC被分为两组: <75%组和≥75%组。采用多元逻辑回归分析评估RC与UACR的相关性。 结果 在模型1‐5中，RC显示出显著的校正后优势比(OR)。尽管模型5中校正了所有混杂因素，RC和UACR仍然显著相关，并且与男性相比，这种相关性在女性中更为显著(对于所有受试者:OR: 1.117, 95% CI: 1.063‐1.176, P < 0.001；对于女性受试者:OR: 1.092, 95% CI: 1.128‐1.161, P = 0.004；对于男性受试者:OR: 1.085, 95% CI: 0.998‐1.194, P = 0.088)。对于5.6≤空腹血糖< 7.0 mmol/L或7.8≤餐后血糖< 11.1 mmol/L，24≤体重指数(BMI)< 28 kg/m2，120≤收缩压< 140mmHg和/或80≤舒张压< 90mmHg的受试者，RC和UACR的相关性更加显著。 结论 在中国社区，RC和UACR显著相关，并且这种相关性在女性中比在男性中更加显著。在较高的RC水平下，血压、BMI、血糖处于临界值的患者，RC与UACR的相关性更显著。 Highlights This is the first multicenter, large‐sample and cross‐sectional study of the relationship between RC and urinary albumin to creatinine ratio (UACR) in the Chinese community adults. RC is highly correlated with UACR, and at high RC level, the patients with critical values of blood pressure, BMI, and blood glucose has a more significant correlation between RC and UACR.